2018
DOI: 10.1016/j.ijpharm.2017.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gold nanoparticles interaction with mucins: A spectroscopic-based study

Abstract: The interaction between two mucin types (mucin from porcine stomach - PGM and mucin from bovine submaxillary glands - BSM) and gold nanoparticles (GNPs) of various size (5, 20 and 40 nm) and functionalization (with cysteamine or thioglycolic acid) was studied under physiological conditions, in order to investigate the affinity of the nanoparticles to the proteins. Different methods are employed to monitor the interactions: UV-vis and fluorescence spectroscopy, fluorescence lifetime, circular dichroism and tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…102 Barbero et al investigated the interaction of mucins of two types with Au NPs of three sizes and different capping ligands (cysteamine or thioglycolic acid). 103 They found that the affinity of proteins to NPs is affected to a greater extent by the capping agent rather than the size. The proteins showed the least affinity toward positively charged NPs.…”
Section: K Pmentioning
confidence: 99%
“…102 Barbero et al investigated the interaction of mucins of two types with Au NPs of three sizes and different capping ligands (cysteamine or thioglycolic acid). 103 They found that the affinity of proteins to NPs is affected to a greater extent by the capping agent rather than the size. The proteins showed the least affinity toward positively charged NPs.…”
Section: K Pmentioning
confidence: 99%
“…14 Ultimately, drug diffusion and mucus clearance mechanisms are hampered and bacteria find a suitable environment to establish and proliferate that results in lung failure. Different studies have reported chemical binding of different entities to mucin that has direct influence over nanoparticle penetration 15,16 and reduced antibacterial potential of colistin, 17 among others. 18 Sputum -expectorated mass that contains mucus, blood, saliva, among others -is often considered as a first rough ex vivo model of CF mucus due to the low invasiveness to retrieve it when compared to physiological mucus.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaled tobramycin associated with aztreonam lysine is usually the first line of treatment for early infections. The affinity of some drugs for mucin has been previously studied using spectroscopic methods by Pontremoli et al (Pontremoli et al, 2015), and by chromatographic methods by Gargano et al (Gargano et al, 2014), whereas Barbero et al have investigated the interactions of both carbon nanotubes (CNTs) and gold nanoparticles (GNPs) with mucin (Barbero et al, 2018(Barbero et al, , 2016). Yet, much needs still to be uncover about mucin-drugs interaction and the physico-chemical parameters that govern the affinity of drugs for mucin.…”
Section: Introductionmentioning
confidence: 99%